Case report: Dentigerous Cyst and Canine Impaction at the Orbital Floor - Hutomo, Ferdian rizky; Pratiwi, Ellen Satya; Kalanjati, Viskasari P; Rizqiawan, Andra (Folia Medica Indonesiana, 2019)
Dentigerous cysts are cysts of the epithelial lining of the jaws derived from the dental follicle of unerupted teeth. These cysts are often found during routine radiographic examination along with unerupted teeth. Dentigerous cysts are usually asymptomatic unless the size becomes large, thus causing swelling. This case report describes the management of dentigerous cyst in the upper left canine region with canine impaction to the orbital floor. Dentigerous cyst was treated with cyst enucleation but the impacted canine was not taken because of the magnitude of risk that can occur which was a disruption to the eye muscle. Conclusion. Treatment of dentigerous cysts can be performed by enucleation technique and management related the impacted tooth at the orbital floor needs a further evaluation consideration.